Pengaruh Permainan Tradisional Engrang Batok Kelapa Terhadap Kemampuan Motorik Kasar Anak - Reski Aulia; Didik Purwanto; Amrullah Amrullah; Andi Agusniatih (Universitas Hamzanwadi, 2025)
The main problem in this study was the low gross motor skills of children in Group B2 at Cendekia Tadulako Kindergarten, particularly in terms of leg muscle strength, balance, and walking speed. The purpose of this study was to analyze the effect of playing the traditional coconut shell game on improving children's gross motor skills in these three aspects. The study used a quasi-experimental method with a one-group pretest-posttest design. The sample consisted of 10 children selected through saturation sampling. Data were collected through observation using validated instruments and analyzed descriptively and inferentially using the Wilcoxon Signed Rank Test. The results showed a significant improvement. The percentage of children in the Very Good Development (VGD) category increased from 0% to 90% for leg muscle strength, from 0% to 50% for balance, and from 0% to 40% for walking speed. The average gross motor score rose from 5.70 to 10.20. Statistical tests produced a significance value of 0.005 (p < 0.05). The conclusion of this study proves that the traditional coconut shell engrang game is effective and significant in improving the gross motor skills of early childhood, so it is recommended as a contextual learning medium in the PAUD curriculum.